2022
DOI: 10.1021/acsnano.2c01993
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Polyester Nanoparticles Trigger Adverse Events in a Large Animal Model of Trauma and in Naı̈ve Animals: Understanding Cytokine and Cellular Correlations with These Events

Abstract: Intravenously infusible nanoparticles to control bleeding have shown promise in rodents, but translation into preclinical models has been challenging as many of these nanoparticle approaches have resulted in infusion responses and adverse outcomes in large animal trauma models. We developed a hemostatic nanoparticle technology that was screened to avoid one component of the infusion response: complement activation. We administered these hemostatic nanoparticles, control nanoparticles, or saline volume controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Later, demonstration of complement activation by Doxil ® (a long-circulating liposome formulation with encapsulated doxorubicin) [ 34 ] generated much interest in studying complement activation properties of different nano- and micro-particles (reviewed in [ 9 , 22 , 35 , 36 ]). Since then, this trend has continued with a diverse range of organic and inorganic materials [ 37 43 ]. Our own efforts in complement mapping have included lipid nanoparticles (including liposomes of different phospholipid composition and bilayer characteristics, and a wide range of non-lamellar liquid crystalline aqueous nanodispersions such as cubosomes and hexosomes), tumour cell-derived exosomes, polymeric nanoparticles, micelles, metallic (e.g., iron oxide) nanoparticles, dendrimers, hydrogels, carbon nanotubes, graphene oxide, and archaeal viruses (reviewed in [ 9 , 22 , 36 ]).…”
Section: Complement Responses To Nanomaterials Nanopharmaceuticals An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, demonstration of complement activation by Doxil ® (a long-circulating liposome formulation with encapsulated doxorubicin) [ 34 ] generated much interest in studying complement activation properties of different nano- and micro-particles (reviewed in [ 9 , 22 , 35 , 36 ]). Since then, this trend has continued with a diverse range of organic and inorganic materials [ 37 43 ]. Our own efforts in complement mapping have included lipid nanoparticles (including liposomes of different phospholipid composition and bilayer characteristics, and a wide range of non-lamellar liquid crystalline aqueous nanodispersions such as cubosomes and hexosomes), tumour cell-derived exosomes, polymeric nanoparticles, micelles, metallic (e.g., iron oxide) nanoparticles, dendrimers, hydrogels, carbon nanotubes, graphene oxide, and archaeal viruses (reviewed in [ 9 , 22 , 36 ]).…”
Section: Complement Responses To Nanomaterials Nanopharmaceuticals An...mentioning
confidence: 99%
“…These observations, strongly suggest an important role for PIMs as effector cells in directing cardiopulmonary distress, particularly on robust nanoparticle clearance from the systemic circulation. Collectively, these observations have generated controversy regarding pig as a valid model for studying human infusion-reactions to nanopharmaceuticals [ 22 , 26 , 43 , 109 , 110 , 121 125 ].…”
Section: Infusion Reactions To Nanoparticles and Nanopharmaceuticalsmentioning
confidence: 99%
“…For scanning electron microscopy (SEM), crosslinked samples were swollen overnight as described above and then lyophilized for 24 h before coating with Au/Pd (60:40) using a Cressington 108 (Cressington) before imaging. Imaging was performed via FEI NovaNano SEM 450 (HV: 5 kV, magnification: 2000×) [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, after these PLGA nanoparticles were applied in a porcine model of trauma, the results showed that these nanoparticles would trigger complement activation and vasodilation, leading to a rapid drop in blood pressure, blood gas changes, and ultimately, increased bleeding. 103 So Nuzhat Maisha et al 76 developed another block copolymer based on poly(lactic acid) (PLA)-PEG nanoparticles (hNPs) with two molecular weights of PEG that led to no measurable complement activation in vitro. The porcine polytrauma model indicated that hNPs could promote clotting and would not activate complement.…”
Section: Synthetic Hemostatmentioning
confidence: 99%